CLOVER: The CMB Polarization Observer - Maffei, B.; Ade, P.A.R.; Calderon, C.; Challinor, A.D.; De Bernardis, P.; Dunlop, L.; Gear, W.K.; Giraud-Héraud, Y.; Goldie, D.J.; Grainge, K.J.B.; Isaak, K.G.; Johnson, B.; et al. (HAL CCSD, 2004)
We present a new, fully-funded ground-based instrument designed to measure the B-mode polarization of the Cosmic Microwave Background (CMB). The concept is based on three independent sub-systems operating at 90, 150 and 220 GHz, each comprising a telescope and a focal plane of horn-coupled background-limited bolometers. This highly-sensitive experiment, planned to be based at Dome C station in Antarctica, is optimised to produce very low systematic effects. It will allow the detection of the CMB polarization over angular multipoles 20